Crossoglossa sotoana (Orchidaceae: Malaxideae), a new species honoring the late Mexican botanist, Miguel Ángel Soto Arenas - Pupulin, Franco; Karremans, Adam P. (Lankesteriana: International Journal on Orchidology, 2010)
Crossoglossa sotoana, a new species from Costa Rica, is described and illustrated. It is compared with Ecuadorian C. barfodii, from which it differs by the strongly undulate margins of the leaves, the resupinate flowers, the shorter and congested inflorescence, the porrect, incurved petals, the obovate-subpandrate lip and the callus composed by two transversely rectangular lamellae. It can be distinguished from C. boylei, also from Ecuador, by its shorter inflorescence, the ligulate petals and the shortly caulescent plants.